Implementation of the Integrity Zone Development Program towards a Corruption-Free Area and a Serving Clean Bureaucracy Region - Pratama, Prasetya Eka; Kamil, Muhammad; Salahudin, Salahudin (Government Studies of Muhammadiyah Malang University/AIPPTM, 2019)
Government bureaucracy is an institution responsible for carrying out the functions of public services, community empowerment to the development of a country, so its presence is very crucial in supporting the state administration system. In reality, government bureaucracy has quite complicated issues, namely the widespread acts of corruption and public services that have not been maximized. Therefore, the Central Government's attempts to address current issues through Ministry of Empowerment of State Apparatus and Bureaucracy Reform to resolve existing problems are implementing an integrity zone development program, both at the central and regional levels. The program aims to create a corruption-free government bureaucracy and enhance the quality of public services. The research method used is descriptive qualitative. Methods for collecting data are through observation, interviews, and documentation. The theory used in this study is the Edwards III model's policy implementation theory, which consists of communication factors, implementing factors, human resource factors, and bureaucratic structure factors. The results of the study found that the Program had been implemented in the Malang Regional Tax Service Agency. The obstacles encountered are in the bureaucratic culture, human resources and public service systems that apply. The researchers' suggestion is that there must be further innovation and periodic supervision of agencies so that the implementation of the program has good results in implementing of bureaucratic reform, especially in Malang City.